Information Technology and the Teaching of History: The Problems of Pedagogic Innovation. Issue 1 (1st December 2001) - Morante, Jesús Romero
In this article, with the conceptual and empirical support gleaned from various investigations, including those carried out by the author himself, we shall argue that the apparently indisputable relationship between computer technology and educational innovation is neither obvious nor necessary. The aim is to shed light on the problems faced by the latter and on some of the conditions that should be met to make it possible. We shall emphasise those determining factors that are specifically pedagogic, by means of an original theoretic and heuristic category: the principle of double contextualization.